Aplikasi Resin Silika Gel-GPTMS (Glisidoksilpropiltrimetoksisilan) Termodifikasi Sulfonat sebagai Fasa Diam pada Analisis Ion Logam K⁺ Menggunakan Kromatografi Ion - Agustiya, Sabay; Oktavia, Budhi (TSAQOFAH, 2025)
The limited adsorption capacity and chemical stability of pure silica pose challenges to the efficiency of metal ion separation via ion exchange mechanisms. This study aims to enhance the performance of silica by surface modification using γ-glycidyloxypropyltrimethoxysilane (GPTMS) and the introduction of sulfonate groups (–SO₃⁻) as active ion-exchange sites. The modification process involved a silanization reaction between silica and GPTMS, followed by functionalization with 4-amino-5-hydroxy-2,7-naphthalenedisulfonic acid, resulting in sulfonate-modified silica gel-GPTMS material. The performance of the material was evaluated using Ion Chromatography (IC) with tartaric acid and methanesulfonic acid as mobile phases under various eluent types and concentrations, a flow rate of 0.2 mL/min, and 5-minute sonication prior to sample injection. The results showed that methanesulfonic acid provided the highest effectiveness due to its ability to maintain a stable H⁺ ion concentration, thereby enhancing ion exchange between the –SO₃⁻ groups on the resin and K⁺ metal ions in the sample. The modified silica material exhibited high structural stability, strong affinity for metal ions, and sharp, symmetrical chromatographic peaks. Thus, GPTMS- and sulfonate-based silica modification is proven effective in improving the selectivity and efficiency of K⁺ ion separation through ion exchange mechanisms.